Rancangan Pembelajaran Berbasis Projek Program Studi Rekayasa Keamanan Siber Politeknik Negeri Batam - Nelmiawati Nelmiawati; Uuf Brajawidagda (JURNAL INTEGRASI, 2021)
Project-Based Learning (PBL) is a learning method that is based on Student-Centered Learning activities by conducting active exploration of learning and solving existing problems. The PBL method has been believed in increasing student motivation, competence and soft skills. This is the basis for Cyber Security Engineering Study Program, Informatics Engineering Department, Politeknik Negeri Batam to transform, develop conventional-based learning towards PBL. Existing PBL-based learning implementations also vary depending on the project, problem, or product produced. This study provides an overview of the PBL design by providing examples of projects that can be carried out, as well as the stages of implementing PBL that follow the industry standards (hardware, software, services) through Agile method. This is the first step in realizing the implementation of PBL in the study program so that it can improve student soft skills and hard skills in solving problems especially in Cyber Security field.